Smart alternating room / Amerrudin Daud & Muhamad Zuhaili Muhamad Nasir - Daud, Amerrudin; Muhamad Nasir, Muhamad Zuhaili (2015)
In this project we are use it for a safety precaution. This project will be a safety project because in this project, we doesn't need a switch to on or off all application in the room. Then, with this project, it also easily for parent or lecture to monitoring a number of person that have in the room at once time. Next, it also easily to handle because when the temperature is suddenly increase, the fan in this system will automatically on when the temperature is reach at the limit. Then, this project also can reduce a cost of electrical because the system will off automatically when there are no people in the room.